Long non-coding RNAs involved in Drosophila development and regeneration. - Camilleri-Robles, C.; Amador, R.; Tiebe, M.; Teleman, A.A.; Serras, F.; Guigó, R.; Corominas, M. (NAR genomics and bioinformatics, 2024)
The discovery of functional long non-coding RNAs (lncRNAs) changed their initial concept as transcriptional noise. LncRNAs have been identified as regulators of multiple biological processes, including chromatin structure, gene expression, splicing, mRNA degradation, and translation. However, functional studies of lncRNAs are hindered by the usual lack of phenotypes upon deletion or inhibition. Here, we used Drosophila imaginal discs as a model system to identify lncRNAs involved in development and regeneration. We examined a subset of lncRNAs expressed in the wing, leg, and eye disc development. Additionally, we analyzed transcriptomic data from regenerating wing discs to profile the expression pattern of lncRNAs during tissue repair. We focused on the lncRNA CR40469, which is upregulated during regeneration. We generated CR40469 mutant flies that developed normally but showed impaired wing regeneration upon cell death induction. The ability of these mutants to regenerate was restored by the ectopic expression of CR40469. Furthermore, we found that the lncRNA CR34335 has a high degree of sequence similarity with CR40469 and can partially compensate for its function during regeneration in the absence of CR40469. Our findings point to a potential role of the lncRNA CR40469 in trans during the response to damage in the wing imaginal disc.